Smartphone in-Class Use and Academic Performance: A Case from the South East European University in North Macedonia - Sadri Alija; Jusuf Zeqiri; Veronika Kareva (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Virtual Conference, 10-12 September 2020, 2020)
Nowadays, it is difficult to imagine life without a smartphone anywhere in the world. It is an inevitable phenomenon of the modern society and influences all spheres of existence from a psychological, social, educational and technological perspective. However, despite the many benefits it brings, excessive use of smartphones can have some adverse effects. The purpose of this paper is to investigate the impact of in-class smartphone use on students' academic performance. Students from the South East European University (SEEU) in North Macedonia participated in the study through an online survey. We aimed to provide answers to the following questions: How smartphones are used in class? Does that use to contribute to learning that is more successful or distract students from it? What kind of other effects do smartphones have on students while in class? The results have confirmed the hypothesis that in -class smartphone use negatively affects student academic performance measurable through the number of European Credit Transfer System (ECTS) credits awarded and students' grade point average (GPA). Some other negative effects have also been identified. Recommendations based on findings might be useful for policymakers, higher education management and professors in order to provide some ways to regulate the use of smartphones in class.
Keywords: A12; 330; smartphones; higher education; academic performance; influence